Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1002/ejic.200600663
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and Nickel Oxide Architectures in Metal Carboxylate Frameworks: From Coordination Polymers to 3D Inorganic Skeletons

Abstract: This microreview is devoted to the synthesis and properties of nickel and cobalt polycarboxylates, which are classified in terms of the geometries of the organic moieties. It is divided into three main sections — dicarboxylates, tricarboxylates and tetra‐ and hexacarboxylates — and discusses the extreme diversity of these architectures. Numerous topologies can be obtained, ranging from coordination polymers to 3D inorganic skeletons. This microreview begins with the widely studied cobalt succinate system, for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 68 publications
(69 reference statements)
0
32
0
Order By: Relevance
“…It is known that the presence of infinite M-O-M connectivities in metal dicarboxylate structures enables the electronic and magnetic exchange in one, two 0932-0776 / 10 / 0600-0695 $ 06.00 c 2010 Verlag der Zeitschrift für Naturforschung, Tübingen · http://znaturforsch.com or three dimensions [1], but the M-O-C-O-M pathway also needs to be taken into account for weak coupling [16]. Furthermore, it has ben reported that magnetic exchange interactions through hydrogen bonds are also possible [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the presence of infinite M-O-M connectivities in metal dicarboxylate structures enables the electronic and magnetic exchange in one, two 0932-0776 / 10 / 0600-0695 $ 06.00 c 2010 Verlag der Zeitschrift für Naturforschung, Tübingen · http://znaturforsch.com or three dimensions [1], but the M-O-C-O-M pathway also needs to be taken into account for weak coupling [16]. Furthermore, it has ben reported that magnetic exchange interactions through hydrogen bonds are also possible [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has ben reported that magnetic exchange interactions through hydrogen bonds are also possible [17]. Because of the diversity of the inorganic networks and their complexity, metal carboxylate frameworks show different and usually extremely complicated magnetic behavior [16].…”
Section: Introductionmentioning
confidence: 99%
“…[16] These examples show that 3D inorganic MOFs are more specific to small, flexible carboxylates. [17] Previously, we studied relations between synthetic parameters (metal/succinate ratio, pH, concentration) and observed architectures for cobalt and nickel succinates. [17,18] In the case of cobalt, we demonstrated that condensation of the inorganic species increased with increasing temperature and pH, and this led to seven cobalt succinate topologies.…”
mentioning
confidence: 99%
“…[17] Previously, we studied relations between synthetic parameters (metal/succinate ratio, pH, concentration) and observed architectures for cobalt and nickel succinates. [17,18] In the case of cobalt, we demonstrated that condensation of the inorganic species increased with increasing temperature and pH, and this led to seven cobalt succinate topologies. [18] Comparison of these compounds to known nickel succinates indicates that the phases that occur at lower temperatures tend to be isostructural (consistent with other Co II and Ni II coordination polymers) [19,20] while the hydrothermal phases differ significantly.…”
mentioning
confidence: 99%
See 1 more Smart Citation